Transferência de estado quântico em sistemas de cavidades acopladas - Almeida, Guilherme Martins Alves de (2016)
The prospect of simulating many-body quantum phenomena in coupled high-quality optical cavities has attracted a lot of interest over the past few years. The major advantages are twofold. First, this approach allows a high degree of control and addressability of individual sites and, second, the composite nature of particles, now involving mixed atomic and photonic excitations, namely polaritons, paves the way to the realization of novel strongly correlated regimes of light and matter. Despite being promising quantum simulators, cavity networks are also suited platforms for distributed quantum information processing and quantum communication. This thesis comprises two studies on coupled-cavity systems described by the Jaynes-Cummings-Hubbard model. Particularly, here we introduce protocols for quantum-state transfer and control in two different structures. The first study deals with a one-dimensional coupled-cavity array where each cavity interacts with a single atom. For a staggered pattern of inter-cavity couplings, a pair of field normal modes, each bi-localized at the array ends, arises. A rich structure of dynamical regimes can hence be addressed depending on which resonance condition between the atom and field modes is set. We show that this can be harnessed to carry out high-fidelity quantum-state transfer of photonic, atomic or polaritonic states. Moreover, by partitioning the array into coupled modules of smaller length, the QST time can be substantially shortened without significantly affecting the fidelity. Further, we explore the dynamics of photonic and atomic excitations on an Apollonian network under different atom-photon interaction regimes. We show that the normal-mode spectrum spanned by this kind of network induces a non-trivial propagation dynamics depending on connection degree among nodes, thereby being useful for connecting different quantum-network users. Our results are driven towards communication protocols in quantum networks comprised of light-matter interfaces, thus paving the way for large-scale quantum information processing.